Functional Condition Rating Segment Sragen Ring Road South, Central Java Province - Rendy D. Pangesti; Ary Setyawan; Budi Yulianto (Institut Teknologi Sepuluh Nopember, 2017)
Assessment of pavement condition is functionally the most important aspect in determining road maintenance and repair activities, so that the financing can be monitored properly. There are two methods in handling the road assessment, ie visually and using tools. Visual assessment can use PASER and PCI. While IRI is a road assessment using Roadroid (Android Smartphone App) tool, where the tool will be used as national reference to get IRI value, because the cost is cheaper and effective. Therefore there needs to be a correlation between the three methods. Correlation in this research is divided into three, namely the correlation of PASER value with PCI, PASER with IRI, and PCI with IRI. The research location used as research object is South Ring Road Sragen. The result of the research was obtained, road assessment using PASER method with PCI resulted correlation value of pearson 0,51. Assessment of PASER with IRI has a correlation value of pearson -0,14. While the value of PCI with IRI yield correlation value pearson -0,23. The value of the correlation coefficient between PASER and PCI has the highest value, since it has a nearly equal assessment approach by measuring the damage visually. The correlation of PCI with IRI is higher than PASER with IRI, thus proving that PCI assessment is more recommended because it can accommodate all types of road damage.